Cybersecurity Snapshot: Google, Twitter, and Other Online Databases - S Rawal, Bharat; Eberhardt, Gabrielle; Lee, Jaein (Journal of Advanced Computer Science & Technology, 2016)
Every day, millions of attacks are carried out on the networks and computer systems. In recent years, these numbers have increased dramatically. All it requires is one success for a hacker to gain unauthorized access and data, but for administrators, it is a constant battle to protect what is rightfully theirs. In this paper, we look into how these attacks have increased, what the studies of various databases and reports say on how and what types of data are being breached, who is breaching them, and how they are breaching the systems. Also, we propose various unconventional ways to prevent these attacks from happening in the future. Furthermore, this paper lists the top 26 bug-fix times reported in the Google Security Research Project (GSRP). This article brings to light reoccurring cyber threats, challenges associated with these threats, and emerging trends in the domain of cyber security.